2018
DOI: 10.1038/cmi.2017.168
|View full text |Cite
|
Sign up to set email alerts
|

Interferon-β induced in female genital epithelium by HIV-1 glycoprotein 120 via Toll-like-receptor 2 pathway acts to protect the mucosal barrier

Abstract: More than 40% of HIV infections occur via female reproductive tract (FRT) through heterosexual transmission. Epithelial cells that line the female genital mucosa are the first line of defense against HIV-1 and other sexually transmitted pathogens. These sentient cells recognize and respond to external stimuli by induction of a range of carefully balanced innate immune responses. Previously, we have shown that in response to HIV-1 gp120, the genital epithelial cells (GECs) from upper reproductive tract induce a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 55 publications
1
11
0
1
Order By: Relevance
“…The finding that acute HIV‐1 exposure upregulates GPB5 transcripts in primary endometrial GECs may indicate that GPB5 may also have a similar role in inhibiting HIV‐1 in the FGT. The upregulation of HIV‐1 restriction factors may be mediated by activation of TLR‐2 on endometrial GECs, that induce biologically active IFN‐β and ISGs with anti‐viral and mucosal barrier protective effects, as shown in our recent study . Thus, the outcome of HIV‐1 exposure in the FGT could be determined by the net effect of inflammatory and anti‐viral pathways.…”
Section: Hiv‐1 and Epithelial Barriersupporting
confidence: 51%
“…The finding that acute HIV‐1 exposure upregulates GPB5 transcripts in primary endometrial GECs may indicate that GPB5 may also have a similar role in inhibiting HIV‐1 in the FGT. The upregulation of HIV‐1 restriction factors may be mediated by activation of TLR‐2 on endometrial GECs, that induce biologically active IFN‐β and ISGs with anti‐viral and mucosal barrier protective effects, as shown in our recent study . Thus, the outcome of HIV‐1 exposure in the FGT could be determined by the net effect of inflammatory and anti‐viral pathways.…”
Section: Hiv‐1 and Epithelial Barriersupporting
confidence: 51%
“…Indeed, epithelial cells from both the upper and lower FGT have been reported to activate signaling pathways following pathogen exposure ( Ferreira et al, 2013 ; Nazli et al, 2010 , 2009 ). Furthermore, our group recently demonstrated that HIV-1 gp120 ( Box 1 ) signaling through TLR2 induced interferon β (IFN-β) production in genital epithelial cells, which had an anti-inflammatory activity and protected the function of the epithelial barrier ( Nazli et al, 2018 ). In addition to inflammatory cytokines, cervicovaginal epithelial cells are known to produce AMPs, including defensins ( Box 1 ), secretory leukocyte protease inhibitor (SLPI), lysozyme, lactoferrin and elafin ( Box 1 ) ( Nguyen et al, 2014 ; Wira et al, 2005 ).…”
Section: Immunity In the Lower Female Genital Tractmentioning
confidence: 99%
“…However, cervical epithelial cells can detect and react to the virus with recent work detecting IFN being produced mainly on the basal interface of the epithelium in response to HIV exposure. 49 IFN , in this context, protects the epithelial barrier against HIV-mediated damage, which could prevent the HIV from reaching its target cells and thus preventing infection. Once the epithelial barrier is crossed, HIV-1 infects its preferred host cells, CD4+ T cells, dendritic cells and macrophages, where a considerable innate immune response is observed.…”
Section: Hivmentioning
confidence: 99%
“…HIV induces IFN in uterine epithelial cells to protect tight junctions. 49 IFN IFN prevents HIV infection in epithelial, T-cells, and macrophages. 59,60 Rhesus macaques IFN /IFN Simian-HIV induces a primary response includes proinflammatory cytokines, whereas IFN /IFN were induced in a secondary response.…”
Section: Ifnmentioning
confidence: 99%